Security of Tenure in Egypt: Policies and Challenges - Eweida, Arig (AUC Knowledge Fountain, 2023)
This thesis explores a set of urban laws and policies adopted in the past decade in Egypt regarding their possible effect on security of tenure as an element of the right to housing. The past decade has witnessed a legislative focus on formalizing tenure rights coupled with policies aiming at redevelopment of informal settlements, infrastructure projects and lately a goal of eliminating unplanned areas by 2030. This research attempts to untangle what these laws and policies could mean for a country with 40% of its housing being informal. It builds on a rich literature on titling programs in developing countries to offer a deeper understanding of the limitations of such programs and their effect on the informal security of tenure and perceived security. The thesis relied on semi structured interviews with experts and stakeholders and content analysis of laws, reports, and court decisions to investigate how Egypt fares regarding internationally accepted indicators of security of tenure. The findings suggest a lack of institutional competency to carry out titling procedures and a possibly negative effect on perceived tenure. The results show good achievements on structural indicators and access to justice in cases of loss of tenure but raise concerns regarding their application on the ground.